(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Zulaika E, Utomo MAP, Pangestu AS, Alami NH, Shovitri M, Prasetyo EN, Setiawan E, Luqman A, Kuswytasari ND, Irawan C. 2021. Novel carbonatogenic bacterial strain isolated from limestone quarry in East Java, Indonesia to improve concrete performance. Biodiversitas 22: 3890-3898. Carbonatogenic bacteria can precipitate CaCO3 in the form of calcite, aragonite, or vaterite. Calcite has the potential to be applied for strengthening concrete structures. This research aims to explore several new bacterial strains that can precipitate calcium carbonate leading to produce calcite and could be useful for strengthening concrete structures. Soil and stalactite samples were taken from a well-known limestone quarry in East Java, Indonesia. The isolated bacteria species were identified using 16S rRNA gene sequences. CaCO3 crystal properties were characterized using X-Ray Diffraction and Scanning Electron Microscopy. Six novels isolated CaCO3 precipitating bacterial strains; Bacillus huizhouensis JA1; B. galactosidilyticus JB3; B. niacini AK4, B. lentus SU1, Lysinibacillus macroides JB2, and Sporosarcina soli JA4 were successfully isolated and have the potential to enhance concrete strength. All isolates were able to produce CaCO3 in calcite form except B. galactosidilyticus JB3. The experimental concrete with the addition of bacterial cells showed higher compressive strength and maximum load compared to control concrete and met the requirements for building construction so that it could be applied for building structure materials.